STUDY ON AREA RAINFALL CALCULATION METHOD IN A COAL MINE - Prasetya Putra, Gigih
Rain is a natural phenomenon that greatly affects the productivity of coal mines with an open pit mining system. When it rains, operating activities must be stopped immediately for safety reasons so the production targets often fail to be achieved. Besides that, consideration of rain factor is important when designing a mine. The regional rainfall calculation method used in the design process is specific for each mining area. Rain characterization will facilitate the analysis of rain factors for design purposes in the mine area. The PT KPC Sangatta site has an area of 48,466 hectares. It has 15 rain stations and 2 weather stations, so it is interesting to analyze its rain characteristics. K-Means clustering method, annual isohyet maps, monthly windrose diagrams, classification of wet months and dry months, and even rainfall values are used in analyzing the characteristics of the rain. Based on K-Means Clustering there are 4 cluster in PT KPC site Sangatta. In determining the appropriate regional rainfall method at the PT KPC Sangatta site an indirect comparison is carried out. Several scenarios with different spatial data availability were created to evaluate the variability. The GORE and BALANCE index are used to compare the estimated regional rainfall values from these scenarios. In cluster 1, two scenarios were created and in clusters 2 and 3, three scenarios were created. From the results the order of the clusters that have the largest to the smallest rainfall is cluster 2, 1, 3, and 4. The direction of the surface wind is dominated by the North-West (NW) quarter. The evenness value of rain in the same cluster is higher than between clusters. From the results of testing the GORE index, on cluster 1, the isohyet method estimates the rainfall better than the Thiessen polygon method and in clusters 2 and 3 the Thiessen polygon method estimates the rainfall better than the isohyet method. The results of testing the BALANCE index on cluster 1 the isohyet method produce overestimated values, in cluster 2 the Thiessen polygon method produces the right value, and in cluster 3 the Thiessen polygon method produces an underestimated value. From this research, the conclusion is that 1) Rainfall in an open coal mine (case study at PT KPC site Sangatta) has spatial characteristics from largest to smallest is cluster 2, cluster 1, cluster 3 and 4 clusters, clusters 3 and 4 are drier than clusters 1 and 2, The surface wind that blows from the NW direction makes the rain bigger in Clusters 1 and 2. Then because there is a height in Cluster 2, the rain in Clusters 3 and 4 tends to be smaller, the evenness value of rain in the same cluster is greater than the evenness value for the entire cluster; 2) The method of calculating regional rainfall according to the characteristics of rain and the number and distribution of rain stations in an open coal mine (case study at PT KPC site Sangatta) is the isohyet method for cluster 1 and the Thiessen polygon method for clusters 2 and 3.